The Impact of Artificial Intelligence (AI) Tools Usage on Buyer Behavior: A Study on Selected Online Pharmacy Apps - Bachina, Lakshmi Priya; Kanagala, Anusha (International Journal of Pharmaceutical Investigation, 2025)
AI technologies affect consumers' attitudes, perceived risk and levels of trust, which in turn affects their purchase behavior. The study explores how AI tools, such as voice search, chatbots and recommendation systems, influence consumer trust, risk perception and purchasing patterns. Purpose The purpose of the study is to investigate how the usage of Artificial Intelligence (AI) tools impact Buyer Behavior on selected online pharmacy apps. It aims to understand the influence of AI-driven features such as recommendation systems, chatbots and personalized marketing on consumer decision-making and purchasing patterns. Design/Materials and Methods/Approach The research employs the Technology Acceptance Model (TAM) to connect AI tool usage with Buyer Behavior, based on a sample of 200 consumers using AI-enabled pharmacy apps in India. Mediation analysis, conducted using Jamovi software, reveals that AI technologies significantly affect Buyer Behavior by mediating the relationship between AI usage and consumer decision-making. Additionally, correlation analysis is performed to examine the relationships between variables such as AI tool usage, perceived ease of use and various aspects of Buyer Behavior, providing further insight into consumer decision-making processes. Findings The findings indicate that the positive influence of AI technology on enhancing consumer trust and mitigating perceived risk, ultimately shaping purchase behavior. These insights provide valuable guidance for professionals in the online pharmacy sector, as well as for legislators and marketers, on leveraging AI tools to optimize customer experiences and satisfaction. Conclusion AI technologies have fundamentally transformed consumer behavior in the online pharmacy space, reshaping how customers search, evaluate and purchase products. Through dynamic pricing, personalized recommendations and responsive customer support, AI has enabled online pharmacy businesses to meet the evolving preferences of modern consumers.
Keywords: AI technology; Buyer Behavior; Decision-making; Online pharmacy apps; Recommendation systems